Community perceptions of mass drug administration for soil-transmitted helminthiasis and schistosomiasis in selected schools in the Philippines - Pauline Joy Lorenzo; Duane Raphael Manzanilla; Dazzle Kane Cortel; Ekaterina Tangog (BMC, 2019)
Abstract Background Soil-transmitted helminthiasis (STH) and schistosomiasis are parasitic infections prevalent in tropical and subtropical countries, such as the Philippines. The prevalence of these infections remain high in certain Philippine provinces, despite established mass drug administration (MDA) programs in endemic communities. This study aimed to understand community knowledge and perceptions of these infections to determine their implications on the current control and elimination strategies, including possible barriers to MDA compliance. Methods The study was conducted in Northern Samar and Sorsogon, two provinces with the highest STH and schistosomiasis prevalence in the country. Focus group discussions with separate parent and children groups were utilized to gather knowledge and perceptions on STH and schistosomiasis causes, symptoms, treatment, and prevention; and on the deworming drugs and overall program implementation. Data collection in Northern Samar were done in August 2017, while the sessions in Sorsogon took place in May 2018. A cultural construction of disease framework will show how several factors affect MDA participation. Results Results showed that participants held mostly correct biomedical notions of the infections and expressed willingness to participate in MDA program. However, reservations remained due to a reported lack of information dissemination, lack of confidence in the drugs used, and widespread fear of adverse side effects. Conclusion Addressing these concerns - improving the conduct of the deworming program, incorporating suggestions from the community, and managing potential adverse events - may help raise MDA participation and encourage better personal preventive practices, reducing STH and schistosomiasis prevalence. Trial Registration N/A